1992
DOI: 10.1104/pp.98.4.1261
|View full text |Cite
|
Sign up to set email alerts
|

RNA Editing of Cytochrome Oxidase Subunit III in Sunflower Mitochondria

Abstract: Direct sequencing of cytochrome oxidase subunit IlIl (coxIll) mRNA with a specific primer confirms RNA editing in sunflower (Helianthus annus) mitochondria. Six instances of mRNA editing could be verified, one of these specific to this species. All the editing events involve C to U transitions in the coxill mRNA causing codon changes that lead to amino acids better conserved in evolution than those encoded in the genomic DNA. This observation confirms RNA editing to be widespread in higher plant mitochondria.a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Saiardi and Quagliariello [28] revealed that direct sequencing of cytochrome oxidase subunit III (coxIII) mRNA with a specific primer confirms RNA editing in sunflower (Helianthus annus) mitochondria. Six instances of mRNA editing could be verified, one of these specific to this species.…”
Section: Introductionmentioning
confidence: 97%
“…Saiardi and Quagliariello [28] revealed that direct sequencing of cytochrome oxidase subunit III (coxIII) mRNA with a specific primer confirms RNA editing in sunflower (Helianthus annus) mitochondria. Six instances of mRNA editing could be verified, one of these specific to this species.…”
Section: Introductionmentioning
confidence: 97%